Incidence and Predictors of Postoperative Atrial Fibrillation after Coronary Artery Bypass Grafting Surgery - Siddiqeh, Musfireh; Khan, Imran; Fayaz, Fakhar-e-; Hasan Kirmani, Syed Muzaffar; Hamshary, Mustafa El; ., Wahidullah; Khan, Zahid M; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the incidence of postoperative atrial fibrillation (POAF) and its predictors after coronary artery bypass grafting (CABG) in an Asian cohort.Study Design: Cross sectional study.Place and Duration of Study: The study was conducted at the department of Cardiothoracic Surgery, Almana Hospital, Al Khobar, Saudi Arabia, which is a tertiary care hospital. The study duration was form Oct 2019 to Dec 2021. Methodology: All the male and female consecutive patients with coronary artery disease undergoing coronary artery bypass grafting (CABG) were included in the study. All the surgeries were performed through median sternotomy using cardiopulmonary bypass. Patients with emergency CABG, off pump CABG and those undergoing multiple procedures were excluded from the study. A total of 220 consecutive patients were included in the study. Patients were followed in the perioperative period. Various variables were recorded on a preformed proforma. Patients were divided into two groups, those who had atrial fibrillation (AF) and those who did not have AF. Data was analyzed using SPPS version 23 (SPSS, Inc., Chicago,IL).Results: The mean age of the patients was 51.50±11 years in the AF group and 49.38±9 years in the no AF group. The incidence of atrial fibrillation postoperatively in our cohort was (n=52, 25%). There was no statistically significant difference between the groups with respect to hypertension and diabetes (p=0.408 and p=0.054) respectively).Conclusion: In spite of a younger population, the incidence of AF in our cohort undergoing CABG is comparable to the international literature. Lack of preoperative β-blockers, statins and low ejection fraction are predictors of new onset POAF.